ABOUT ONE TASK OF OPTIMAL CONTROL OF VARIABLE-MASS PARTICLE MOTION IN GRAVITATIONAL FIELD - Barseghyan, V. R.; Chilingaryan, G. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
A task of priority selection of optimal control actions for control of variable-mass particle motion in gravitational field is discussed. On the basis of obtained results, it is shown by a numerical example that the quality criterion minimization on priority principle results in less value of quality criterion than the minimization in the usual sense.